Review of the U.S. CLIVAR Project Office (National Academies Press, 2004)
A growing appreciation for how variations in climate affect society and the environment has increased the demand for fast and accurate predictions of climate variability. The Climate Variability and Predictability (CLIVAR) program, established internationally in 1995 and expanded to include a U.S. component in 1998, focuses on improving understanding and skill in predicting climate variability on seasonal to centennial time scales. This report evaluates the performance of the U.S. CLIVAR Project Office (PO) in fulfilling its charge from supporting agencies. The report concludes that the project office is vital for coordinating US CLIVAR activities and is effective despite limited resources. It also provides suggestions for enhancing the communications from and visibility of US CLIVAR activities and for developing strategic directions for the future.